PENGARUH GAYA KEPEMIMPINAN, MOTIVASI DAN DISIPLIN KERJA TERHADAP PRESTASI KERJA PEGAWAI PT. TAMAN WISATA CANDI BOROBUDUR, PRAMBANAN DAN RATU BOKO (PERSERO) - Efrat Tirta Wijaya; Candra Vionela Merdiana (Jurnal Fokus Manajemen Bisnis, 2019)
This study aimed to find out: (1) the influence of leadership style toward the work performance of employees in PT. TWC Borobudur, Prambanan & Ratu Boko (Persero), (2) the influence of motivation toward the work performance of employees in PT. TWC Borobudur, Prambanan & Ratu Boko (Persero), (3) the  influence of work  discipline toward the work performance of employees in PT. TWC Borobudur, Pramban an & Ratu Boko  (Persero), (4) the influence of leadership styles, motivation and work discipline simultaneously toward the work performance of employees in PT. TWC Borobudur, Prambanan & Ratu Boko (Persero). The  sample of  this  study was  the  employees  of  PT.  Taman Wisata Candi Borobudur, Prambanan & Ratu Boko (Persero), there were 130 employees  in total, by using the technique of simple insidental sampling. The multiple linear regression model was  used  for  collecting  the  data  in  this  study.  The  test  validity  used in the study was confirmatory factor analysis. From the test result, there were 20 questions fallen, those were the items in questioning: the variable of leadership style with 4 questions in total; 7 questions on the variable of motivation; 6 questions on the variable of work discipline; and  also 3 questions  on  work  performance,  from  22  questions  in  total  and all of the reliable questions. The result from this study showed that the variable on leadership style (X1) had an positive effect toward the work performance of PT. TWC Borobudur, Prambanan & Ratu Boko (Persero)’s employees. The variable of motivation (X2) influenced positively toward the work performance of the employees at PT. TWC Borobudur, Prambanan & Ratu Boko (Persero). The variable of work discipline (x3) had positive effect on the work performance  of  the  employees  at  PT.  TWC  Borobudur,  Prambanan  &  Ratu  Boko (Persero). The variable of leadership style, motivation and work discipline altogether or simultaneously had a significant effect toward the work performance of employee at PT. TWC Borobudur, Prambanan & Ratu Boko (Persero).